Antimicrobial susceptibility study and molecular epidemiology of ceftazidime/avibactam against Pseudomonas aeruginosa collected from clinical patients in PR China (2004–2021). Issue 2 (8th February 2023) - Hu, Yanyan; Chen, Jiawei; Huang, Ling; Liu, Congcong; Zhou, Hongwei; Zhang, Rong
Abstract : Introduction . The increasing prevalence of multidrug-resistant (MDR) Pseudomonas aeruginosa worldwide is a significant global public health concern. Ceftazidime/avibactam (CZA) has been considered a novel promising β-lactam/β-lactamase inhibitor combination antibiotic against difficult-to-treat P. aeruginosa isolates. Big data studies on CZA susceptibility against P. aeruginosa have been limited. Gap statement . Production of metallo-β-lactamases was the most prevalent resistance mechanism for P. aeruginosa against CZA. Aim . To assess the in vitro activity of CZA against P. aeruginosa strains and the relevant resistance mechanisms. Methodology . One thousand three hundred and sixty-three P. aeruginosa isolates were collected from 2004 to 2021. Antimicrobial susceptibility testing was carried out for commonly used antipseudomonal drugs via the broth microdilution method. Polymerase chain reaction (PCR) or whole-genome sequencing were performed to analyse the most common carbapenemase genes. Molecular epidemiology was analysed by uploading the sequencing data to the Center for Genomic Epidemiology website. Results . Antimicrobial susceptibility testing showed that CZA and lipopeptides are the most active antibiotics against P. aeruginosa isolates. PCR and genome sequencing revealed that the most prevalent resistance mechanism for P. aeruginosa against CZA was the production of metallo-β-lactamases. None of the bla PDC mutations were found to be associated with avibactam resistance. Conclusion . Our findings revealed that CZA and lipopeptides are the most active antibiotics against P. aeruginosa isolates. The most prevalent resistance mechanism for P. aeruginosa against CZA was the production of metallo-β-lactamases, and none of the bla PDC mutations were found to be associated with avibactam resistance.